The Influence of Price, Attractiveness, Accessibility on Decisions to Visit PPLH Seloliman Trawas Mojokerto Tourism - Febriana Ayu Widiati; Mas Oetarjo (Universitas Muhammadiyah Sidoarjo, 2022)
This study aims to determine the effect of price, attractiveness, and accessibility on the decision to visit PPLH Seloliman Trawas Mojokerto tourism. This research is a descriptive study using quantitative methods. The data collection technique is by distributing questionnaires to 100 respondents who are tourists who visit PPLH Seloliman Trawas Mojokerto tourism. The analytical technique used in this study is multiple linear regression using SPSS (Statistical Program for Social Science) version 25 for windows. influence the decision to visit PPLH Seloliman Trawas Mojokerto wisata tourism